An Analysis of Students’ Difficulties in Listening Skill: A Case Study on Critical Listening Subject at 2nd Semester of English Education Department Class B in UIN SMH BANTEN - Nurfadilah, Khaerani; Rahmawati, Eulis; Handayani, Selnistia (English Education, Linguistics, and Literature Journal, 2023)
The aims of study were to find out the difficulties that mostly faced by students in learning listening and find out the factors of students difficulties in learning listening. The formulated problems of this study were: (1) What are students’ difficulties found in listening at the student college of the English education department? (2) How the factors that cause the difficulties students’ in listening skill at the student college of the English education department? This study employed the qualitative research approve with case study method. Qualitative method was chosen because this study aims to analysis cases of students difficulties in listening skills. The participants of the research are 29 students from 2nd semester of English education department. Collecting the data of analysis the students difficulties in listening skills were obtained by observation, questionnaire, interviews. The result of the study showed students difficulties in listening skill there are four characteristic. The first characteristic is characteristic of the message, second characteristic of the delivery, the third is characteristic of the listener and the last is characteristic of the environment. Moreover, factors influenced are internal and external factors. Internal factors are physical condition and motivation and external factors are facilitate such as environment, speakers and materials.